High Number of Positive Rapid Plasma Reagin With Low Titers Using the Automated AIX 1000 RPR System. Issue 1 (January 2022) - Palavecino, Elizabeth L.; Soltani, Sohaila; Keller, Ryan; Elliott, Stephanie; McNeil, Candice J.
Abstract : Abstract: This study evaluated the performance of manual rapid plasma reagin (RPR) and automated AIX1000 RPR tests for the diagnosis of syphilis. Manual RPR showed a 3% reactive result compared with 5.8% for the automated test mainly because of RPR reactive results with low titers not confirmed by Treponema pallidum particle agglutination. Abstract : The automated AIX1000 RPR test provides more reactive rapid plasma reagin results with low titers that are not confirmed by Treponema pallidum particle agglutination compared with manual rapid plasma reagin.